'Just hit a button!' – fashion 4.0 designers as cyborgs, experimenting and designing with generative algorithms. Issue 2 (4th May 2022) - Särmäkari, Natalia; Vänskä, Annamari
ABSTRACT: This article investigates algorithmic fashion design approaches in order to explore the ongoing digital transformations in fashion designership. The article asks how the automation of design processes and collaboration with machines affect the authorship and professional boundaries of fashion designers. The article analyses two case studies, the Finnish designer Matti Liimatainen and the Dutch 'digital-only' fashion house The Fabricant, to demonstrate how different ways of combining fashion designers' expertise, creativity and tacit knowledge with programming and/or computer-generated content alter the design process. The article also uses Donna Haraway's metaphor of the 'cyborg' (1985) to explain how digitalisation of the process intertwines designers with digital infrastructures. Two approaches to algorithmic fashion design are identified: generative clothing development and AI-aided digital fashion sketching. It is argued that both approaches involve the characteristics of computerisation/hominisation, re-professionalisation and 'cyborg designer 4.0'.